Water channels in the brain and spinal cord—overview of the role of aquaporins in traumatic brain injury and traumatic spinal cord injury - Overgaard Wichmann, Thea; Hedegaard Højsager, Marie; Hasager Damkier, Helle (Frontiers in Cellular Neuroscience, 2024)
Knowledge about the mechanisms underlying the fluid flow in the brain and spinal cord is essential for discovering the mechanisms implicated in the pathophysiology of central nervous system diseases. During recent years, research has highlighted the complexity of the fluid flow movement in the brain through a glymphatic system and a lymphatic network. Less is known about these pathways in the spinal cord. An important aspect of fluid flow movement through the glymphatic pathway is the role of water channels, especially aquaporin 1 and 4. This review provides an overview of the role of these aquaporins in brain and spinal cord, and give a short introduction to the fluid flow in brain and spinal cord during in the healthy brain and spinal cord as well as during traumatic brain and spinal cord injury. Finally, this review gives an overview of the current knowledge about the role of aquaporins in traumatic brain and spinal cord injury, highlighting some of the complexities and knowledge gaps in the field.